Effects of planting Phragmites australis on nitrogen removal, microbial nitrogen cycling, and abundance of ammonia-oxidizing and denitrifying microorganisms in sediments. Issue 4 (16th February 2016) - Toyama, Tadashi; Nishimura, Yoshiko; Ogata, Yuka; Sei, Kazunari; Mori, Kazuhiro; Ike, Michihiko
Abstract : We examined the effect of planting an emergent aquatic plant ( Phragmites australis ) on nitrogen removal from sediments using a 42-d pot experiment. The experimental pot systems comprised two types of sediments planted with and without young P. australis . Total nitrogen (total N), total dissolved N, and NH4 –N in the sediments decreased markedly after planting. In contrast, those levels decreased only slightly in the unplanted sediments. The decrease in total N in the P. australis- planted sediments was 7–20 times those in the unplanted sediments. Abundances of bacterial 16S rRNA, archaeal 16S rRNA, ammonia-oxidizing bacterial ammonia monooxygenase ( amoA ), ammonia-oxidizing archaeal amoA, and denitrifying bacterial nitrite reductase ( nirK ) genes increased significantly in sediments after planting. Phragmites australis appears to have released oxygen and created a repeating cycle of oxidizing and reducing conditions in the sediments. These conditions should promote mineralization of organic N, nitrification, and denitrification in the sediments. Phragmites australis absorbed bioavailable nitrogen generated by microbial nitrogen metabolism. During the 42-d period after planting, 31–44% of total N was removed by microbial nitrogen cycling, and 56–69% was removed via absorption by P. australis . These results suggest that planting P. australis can increase microbial populations and their activities, and that nitrogen removal can be accelerated by the combined functions of P. australis and microorganisms in the sediment. Thus, planting P. australis has considerable potential as an effective remediation technology for eutrophic sediments.